EDUCATIONAL MODELING WITH SIMULATION FOR THE CONSOLIDATION OF PROFESSIONAL COMPETENCE IN CONTINUING EDUCATION - Santos, Bruna dos; Cruz, Elaine Drehmer de Almeida; Brusamarello, Tatiana; Nazário, Saimon da Silva (Cogitare Enfermagem, 2024)
Objective: to describe the development, application, and evaluation of educational modeling technology with simulation. Method: a methodological study carried out in 2022 in southern Brazil. Nursing and medical leaders and residents took part in two phases (identification of patient safety gaps and definition of educational sub-themes) and 10 stages (learning objectives; theoretical foundation; learner knowledge; scenario design; evaluation and adjustments to the simulation scenario; training of actors and guidance for observers; development of scenes; observation; and debriefing). Results: gaps in patient safety: developing communication between the interprofessional team, understanding the importance of protocols, and including the patient in the care process. Educational technology with simulation was evaluated as a tool that provides the opportunity to replicate and contrast everyday practice with patient safety precepts and to learn. Conclusion: The replicability of the methodology for different contexts and audiences is an important contribution to practice.